فن التفاوض والحوار داخل المؤسسة الاقتصادية - مولاي علي، الزهرة Moulay Ali, Alzahrah (جامعة الجزائر1 بن يوسف بن خدة, 2019)
The individual's acceptance to enter into a relationship with the other requires consensus and harmony in values, ideas and beliefs, it shows clearly during the discussion and exchange of views between the parties of the dialogue. Both parties could reach the possible area of agreement or reach an impasse. In the first case, suggests the existence of an agreement and common objectives between the parties that send into their minds an ability and a strong willingness to enter into an important relationship of their nature: labour relations example The second case, suggests that there is no agreement and communication because of the different interests and objectives of each party of the other, leading to reluctance to engage in a lasting relationship with the other. The worker accepts to join any economic enterprise and enter into labour relations if there is a consensus and harmony between the beliefs and logic of the worker's thinking and his point of view of working with the modern organizational culture prevailing in the enterprise, which vary from one enterprise to another. Can find the worker a work climate that is completely contrary to what he or she expected, he or she must engage in dialogue and negotiation with the company. If we accept the dialogue that results from a situation of difference of opinion and legitimate to each negotiating party. Based on this observation, what are the conditions required for a successful negotiation?
إن قبول الفرد الدخول في علاقة مع الآخر يتطلب وجود التوافق وانسجام في القيم والأفكار والمعتقدات، ويظهر ذلك بشكل جلي أثناء الحوار والنقاش وتبادل الآراء بين الطرفين، قد يصل الطرفين إلى منطقة التوافق المحتملة أو إلى طريق مسدود. ففي الحالة الأولى توحي إلى وجود اتفاق وأهداف مشتركة بين الطرفين التي تبعث في روحهم الاستعداد والإرادة القوية لدخول في علاقة مهما كانت طبيعتها: علاقات العمل مثلا. أما الحالة الثانية توحي إلى عدم وجود اتفاق وتواصل نظرا لاختلاف المصالح والأهداف كل طرف عن الآخر، مما يؤدي إلى نفور الدخول في علاقة دائمة مع الآخر. إن قبول العامل الالتحاق بأي مؤسسة اقتصادية ودخول في علاقات العمل يستدعي وجود التوافق والانسجام بين معتقدات ومنطق التفكير العامل ونظرته للعمل مع الثقافة التنظيمية الحديثة السائدة بالمؤسسة والتي تختلف من مؤسسة لأخرى، قد يجد العامل مناخ عمل مخالف تماما عن ما كان يتوقعه فهو يضطر الدخول في حوار والتفاوض مع المؤسسة. وإذا سلمنا إن قبول الحوار ينطلق من التسليم بواقع الاختلاف في الرأي، وبشرعيته لكل طرف من الأطراف المتفاوضة، ترى ما هي شروط الأساسية لنجاح عملية التفاوض؟
الجزء الرابع: ديسمبر 2019
Keywords: التفاوض الإداري -- علاقات العمل -- إدارة الموارد البشرية -- المؤسسات الاقتصادية -- الجزائر